2021
DOI: 10.1088/1757-899x/1147/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the cutting material on tool wear, surface roughness, and force components for different cutting speeds in face turning of CoCrFeNi high-entropy alloys

Abstract: High-entropy alloys (HEAs) provide advanced properties like a high resistance to corrosion and wear. Concerning this and the elevated material costs wear protection layers are a possible field of application. Finish machining of these layers is necessary to achieve adequate surface properties. In the experimental investigations face turning of high-entropy alloy CoCrFeNi layers generated by spark plasma sintering is regarded. In this context, the influence of the cutting material and the cutting speed is analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, for potential applications, it is still necessary to bridge the gap regarding processability, since publications in this matter are scarce, hence the importance of researching, for example, machining processes on these novel alloys. So far, research on the machinability of HEA systems is limited [18][19][20][21][22][23], with the majority focusing on the Cantor alloy. Gou et al [18] conducted a study on different machining processes on the Cantor alloy, including milling, grinding, mechanical polishing, electrodischarge machining, and electropolishing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for potential applications, it is still necessary to bridge the gap regarding processability, since publications in this matter are scarce, hence the importance of researching, for example, machining processes on these novel alloys. So far, research on the machinability of HEA systems is limited [18][19][20][21][22][23], with the majority focusing on the Cantor alloy. Gou et al [18] conducted a study on different machining processes on the Cantor alloy, including milling, grinding, mechanical polishing, electrodischarge machining, and electropolishing.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a high affection of the subsurface in terms of high microhardness and compressive residual stresses for the milling process. Liborius et al [21] investigated the influence of the tool material (CBN, PCD, CVD diamond, and solid cemented carbide) and cutting speed (100-400 m/min) in the face turning of SPS-fabricated CoCrFeNi, reporting the lowest roughness values and tool wear for CBN 90 tips. Litwa et al [22] investigated the effect of depth of cut, feed per cutting edge, and cutting speed on the Cantor alloy, observing reduced cutting forces at a low depth of cut and feed rate and at high cutting speeds.…”
Section: Introductionmentioning
confidence: 99%
“…The high strength and low thermal of the Ti alloys often cause a high cutting temperature, which significantly influences the machined surface quality and tools lifetime [ 18 ]. Studies on the conventional machining of HEAs have shown that although a good surface quality can be achieved, the lifetime of cutting tools was significantly reduced due to numerous cutting heat and severe wear [ 19 , 20 , 21 ]. While for the RHEAs with a higher strength and hardness, how to process RHEAs is more challenging but important for their engineering applications.…”
Section: Introductionmentioning
confidence: 99%